2021
DOI: 10.1055/s-0040-1722250
|View full text |Cite
|
Sign up to set email alerts
|

The Application of P300-Long-Latency Auditory-Evoked Potential in Parkinson Disease

Abstract: Introduction Parkinson disease (PD) is a degenerative and progressive neurological disorder characterized by resting tremor, stiffness, bradykinesia, and postural instability. Despite the motor symptoms, PD patients also consistently show cognitive impairment or executive dysfunction. The auditory event-related potential P300 has been described as the best indicator of mental function, being highly dependent on cognitive skills, including attention and discrimination. Objective To review the literatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 41 publications
0
5
0
1
Order By: Relevance
“…It is also worth noting that the P1 and N1 components respond to spectral characteristics of a sound stimulus [ 46 ]. Finally, changes in the P300 component can be related to cognitive functions, such as decision-making, attention, discrimination, recognition, integration, focus, and memory [ 41 43 ]. All of this corroborates findings that AT tends to reduce the latency of the P300 component [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is also worth noting that the P1 and N1 components respond to spectral characteristics of a sound stimulus [ 46 ]. Finally, changes in the P300 component can be related to cognitive functions, such as decision-making, attention, discrimination, recognition, integration, focus, and memory [ 41 43 ]. All of this corroborates findings that AT tends to reduce the latency of the P300 component [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…When analyzing the effectiveness of auditory training through the P300, the authors found reduced latency and increased P300 amplitude after the intervention, results that are consistent with the findings of the current study. This potential has been described as the best indicator of auditory function, being highly dependent on cognitive skills, including attention and memory (30) . Therefore, it is believed that there was no statistically significant difference in latency and amplitude of the cognitive potential -P300 in this study, due to the sample n and the great variability of the sample.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have found abnormal ERPs in patients with PDD. The study reported that P3 and N2 latencies in patients with dementia were significantly longer than normal controls, while patients with PD without dementia had only an extended P3 latency [17] . The study found that PD with dementia was significantly longer in P3 latency compared with control groups.…”
Section: Groupmentioning
confidence: 92%